simplify (4x^4y^3)(4x^4)

1 answer

To simplify (4x^4y^3)(4x^4), we can simply multiply the coefficients and add the exponents of the variables.

The coefficient of (4x^4y^3)(4x^4) is 4*4=16.

The variable x has an exponent of 4 in each term, so when we multiply, we add the exponents: x^4 * x^4 = x^(4+4) = x^8.

The variable y has an exponent of 3 in the first term, and no y in the second term, so y^3 * 1 (since there is an implied 1 in the second term) = y^3.

Therefore, the simplified expression is 16x^8y^3.